2022
DOI: 10.1016/j.arth.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A Psycholgical Intervention Delivered by Automated Mobile Phone Messaging Stabilized Hip and Knee Function During the COVID-19 Pandemic: A Randomized Controlled Trial

Abstract: Background We conducted a randomized controlled trial to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) delivered via a mobile phone messaging robot to patients who had their total hip (THA) or total knee arthroplasty (TKA) procedures postponed due to the Covid-19 pandemic. Methods Ninety patients scheduled for THA or TKA who experienced surgical delay due to the Covid-19 pandemic were randomized to the ACT group, receiving 14 days of twice daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the two included studies, the remote interventions were based on mobile applications [ 31 , 32 ]. The interventions used a system of sending text messages as well as more advanced features like displaying short videos or audio records.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the two included studies, the remote interventions were based on mobile applications [ 31 , 32 ]. The interventions used a system of sending text messages as well as more advanced features like displaying short videos or audio records.…”
Section: Resultsmentioning
confidence: 99%
“…For the HOOS JR and KOOS JR, 24% of the ACT group achieved minimal clinically important differences compared to 2.5% in the control group. The authors concluded that the psychological intervention delivered via text messaging improved physical functioning and prevented deterioration in outcome measures reported by patients who experienced an unexpected surgical delay during the COVID-19 pandemic [ 31 ]. Sun et al evaluated the effect of a mindfulness-based mobile health (mHealth) intervention among young adult students with elevated anxiety and/or depressive symptoms compared to a time- and attention-matched social support-based mHealth control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nested qualitative study showed that participants viewed the SMS intervention as a valuable exercise reminder that promoted accountability to the unsupervised exercise program [77]. Another RCT evaluated a psychological intervention delivered via automated SMS in people who had hip or knee joint replacement surgery postponed due to the COVID-19 pandemic [97]. It found that the intervention (two SMS per day for 14 days to encourage pain coping) led to meaningful clinical improvements at 2 weeks, compared to no contact.…”
Section: Short Message Services (Sms)mentioning
confidence: 99%
“…SMS text message-based interventions, in particular, may be most effective in reaching the largest number of consumers, as texts do not require access to the internet, have low technology literacy requirements, and are low cost and familiar, as there is a high current use of text messaging worldwide [16][17][18]. Mobile phone text interventions have demonstrated effectiveness in facilitating health-related behavior change [18,19], helping people to quit smoking [20], improving outcomes in the management of musculoskeletal conditions [21], and even supporting people to manage perioperative pain [17,22].…”
Section: Digital Healthmentioning
confidence: 99%